Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Kreatif Berbasis Video Podcast pada Guru TK, RA, PAUD, dan KB, se Kecamatan Kencong, Jombang, dan Gumukmas - Sinta Bella; Rizqiyah Ratu Balqis; Nur Imamatun Nisa’; Muhyidin (LP3M IAIFA Kediri, 2025)
Podcasts as audio-visual-based learning media offer a solution to monotonous and boring learning, especially at the kindergarten/equivalent level. However, teachers have difficulty in creating and using podcasts as a learning medium. The paradigm that kindergarten/equivalent education is just a place to play often makes teachers trapped in the use of conventional media. As a result, learning becomes less varied and interesting. Therefore, this community service aims, first, to provide insight to kindergarten, RA, PAUD, and KB teachers, in Kencong, Jombang, and Gumukmas Districts about the stages of video podcast production as a creative learning medium. Second, to assist kindergarten, RA, PAUD, and KB teachers, throughout Kencong, Jombang, and Gumukmas Districts in the production of creative learning media based on video podcasts. The community service method used is Service Learning (SL), which is connecting theory in class with real practice in community service. The results of the community service show that teachers understand the stages of production and have increased skills in creating video podcast-based learning media.